Europe and Central Asia Macro Poverty Outlook : Country-by-Country Analysis and Projections for the Developing World - World Bank (Washington, DC, 2022)
This edition of the Macro Poverty Outlooks periodical contains country-by-country forecasts and overviews for GDP, fiscal, debt and poverty indicators for the developing countries of the Europe and Central Asia region. Macroeconomic indicators such as population, gross domestic product and gross domestic product per capita - and where available – other indicators such as primary school enrollment, life expectancy at birth, total greenhouse gas emissions and inflation, among others, are included for each country. In addition to the World Bank’s most recent forecasts, key conditions and challenges, recent developments and outlook are briefly described for each country in the region.